2017
DOI: 10.18632/oncotarget.16279
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-stimulated microRNA expression in mural cells promotes transplantation-induced neointima formation

Abstract: In this study, we tested the possibility that macrophages might contribute to neointima formation by stimulating microRNA expressions in mural cells. Thoracic aortas from F344 rats were transplanted into recipient Lewis rats. Clodronate liposome was used for in vivo macrophage depletion. Using miR-21 as a prototypic example of vascular enriched microRNA, we showed that macrophage depletion reduced the expression level of miR-21, which was upregulated in the allograft. This effect of macrophage depletion was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…21,26 Moreover, our results have demonstrated that targeting adventitial macrophage accumulation and activation may effectively repress transplantation-induced arterial remodeling. 32 It is suggested that activation of the tunica adventitia may have crucial implications in the pathogenesis of transplant vasculopathy (Figure 1). Further investigations are warranted to clarify whether inhibiting adventitial NADPH oxidase and the process of neovascularization may represent new strategies for preventing this disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21,26 Moreover, our results have demonstrated that targeting adventitial macrophage accumulation and activation may effectively repress transplantation-induced arterial remodeling. 32 It is suggested that activation of the tunica adventitia may have crucial implications in the pathogenesis of transplant vasculopathy (Figure 1). Further investigations are warranted to clarify whether inhibiting adventitial NADPH oxidase and the process of neovascularization may represent new strategies for preventing this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treating transplanted vessels with miR-21 antagomir induced a significant reduction in the development of neointima and significantly reduced the inflammatory responses in both media and adventitia. 32 Using in vitro assays, macrophages were found to stimulate miR-21 expression in smooth muscle cells and adventitial fibroblasts via the release of tumor necrosis factor-a, whereas silencing of miR-21 expression attenuated tumor necrosis factoreinduced proliferation, migration, and inflammation in smooth muscle cells and fibroblasts. 32 More important, it was confirmed that systemic depletion of macrophages concomitantly repressed the vascular miR-21 expression and ameliorated transplantation-induced neointimal remodeling.…”
Section: Critical Roles Of Adventitial Macrophage In Transplant Vascumentioning
confidence: 99%
See 3 more Smart Citations